Neural Acceleration for General-Purpose Approximate Programs - Esmaeilzadeh, H.; Sampson, A.; Ceze, L.; Burger, D. (2012 45th Annual IEEE/ACM International Symposium on Microarchitecture, 2012)
This paper describes a learning-based approach to the acceleration of approximate programs. We describe the Parrot transformation, a program transformation that selects and trains a neural network to mimic a region of imperative code. After the learning phase, the compiler replaces the original code with an invocation of a low-power accelerator called a neural processing unit (NPU). The NPU is tightly coupled to the processor pipeline to accelerate small code regions. Since neural networks produce inherently approximate results, we define a programming model that allows programmers to identify approximable code regions -- code that can produce imprecise but acceptable results. Offloading approximable code regions to NPUs is faster and more energy efficient than executing the original code. For a set of diverse applications, NPU acceleration provides whole-application speedup of 2.3× and energy savings of 3.0× on average with quality loss of at most 9.6%.